Strategic Planning for Advanced Nursing Practice - Schober, Madrean (Springer International Publishing : Imprint: Springer, 2017)
This eagerly anticipated book equips readers to understand the dynamics of policy processes, relevant decision-making and the significance of key decision-makers. It also emphasizes the usefulness of negotiation and diplomacy skills in order to support the development of an advanced nursing practice (ANP) initiative that involves the identification of pivotal issues to ensure that nurses unlock their full potential. Topics include a definition of strategic planning, essential factors to bear in mind, and frameworks to use in the context of formulating effective policies. By addressing outcome indicators and research, this volume offers a comprehensive approach to coordinated planning, and will appeal to advanced practice nurses, healthcare planners and policymakers, as well as administrators at hospitals and healthcare institutions.
Keywords: Medicine.; Health promotion.; Social policy.; Economic development.; elektronické knihy; electronic books